Rites and Rights: Lineage Property and Law in Korea - Marie Seong-Hak Kim (L'Atelier du CRH)
This Article sets forth a historical overview of the evolution of lineage property and succession law in Korea from the premodern through contemporary times. The desire to continue the family and safeguard patrimonial integrity is arguably a universal phenomenon, but the primacy of Confucian ancestral rituals during the Chosŏn dynasty (1392-1910), combined with the indigenous kinship structure, created a distinct lineage organization and culture. The strict primogenitary order and postmortem adoption practices ensured agnatic succession through ritual heir, which rendered the concepts of vacant succession and succession in abeyance theoretically irrelevant, if not inconceivable. Korea did not see the rise of joint property-holding corporate clan estates as in China. Under Japanese rule (1910-1945), ritual-based succession and property relations underwent major reconfigurations in law. The evolving colonial jurisprudence on lineage assets and also on the property of the houses that went extinct illustrated the effort of the courts to negotiate between traditional normativity and modern civil law. In modern Korean law, a lineage group is construed as an unincorporated association and disputes over its assets continue to arise. Investigation of lineage property offers an opportunity to explore how Confucian ideology and its precepts have influenced Korean law and history over centuries. It demonstrates that East Asian legal tradition needs to be assessed through comparison of cultural and social realities in different countries, in all their independence and interdependence.